La manifestación de lo general en la comedia según Aristóteles - Cifuentes Acuña, Luis (Revista Chilena de Literatura, 2016)
This work attempts to offer a view on the Aristotle’s idea of generality in comedy, idea developed fragmentarily in his Poetics through a schematic history of the genre.Considering that Aristotle conceives of poetry as a mimetic activity where the general tends to be a defining element in its being a special kind of experience, in this work I will show its grounding and specific features wich will lead us to understand comedy as a specific type of expression of the general. All this will finally lead us to affirm that in Aristotle’s purpose to construe an idea of comedy as opposite to the previous comic form of the lampoon, the general will be a fundamental criterion to understand some key concepts of the genre (as the laughable) and its relationship with New Comedy plays.